О приводимости линейных дифференциальных операторов с неограниченными операторными коэффициентами - Баскаков, А.Г. (Український математичний журнал, 1993)
The results conccraing the reducing of linear dilierential operators wjlh unbounded operator coefficients to differential operators with a simpler structure arc obtained.